E-Commerce Training for Beginner Entrepreneurs in Bireuen District - Zuriani Ritonga; Hayanuddin Safri; Bayu Eko Broto; Sutoyo; Chairul Bariah; Nasution, Atika Aini; Aryani Sairun (PT Inovasi Pratama Internasional, 2022)
Mature this development of business startups Micro, Small, and Intermediate (MSME) supported with technological development. The existence of the industrial revolution 4.0 has a positive impact on developments business world. Utilization of the latest appropriate technology in business development based on in the spirit of an established entrepreneur will be able to optimize the process as well as the results of a business unit that is developed. E-commerce training in the home industry provides benefits to business actors Micro, Small, and Intermediate in Bireuen District for increase turnover sale as well as could develop a business that live it to grow become more big again. The existence of an e-website This commerce customer gets not only from the scope of Bireuen Regency, but also customers can be from outside Aceh, of course it can help the government in improve the economy, especially in the regencies, so that the regencies are open to opportunities for able to compete on a national and international level. Order process, sales process and stock goods can conducted with fast and accurate so that could help monitoring effort and also naturally could increase turnover sale for perpetrator MSME which exists in Bireuen Regency.